2022
DOI: 10.31083/j.jin2101014
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of natural products for the treatment of ischemic stroke

Abstract: Stroke is a leading cause of death and disability world-widely. The incidence rate of stroke has been increasing due to the aging population and lifestyle changes. At present, the only drug approved by the US Food and Drug Administration (FDA) for the treatment of ischemic stroke is tissue plasminogen activator (t-PA), but its clinical application is greatly limited because of its narrow time window and bleeding risk. Natural products have a long history of being used in traditional medicine with good safety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…In addition, the HE and Nissl staining also indicated the neuroprotection of IronQ-labeled MSCs is superior to MSCs and quercetin treatment, respectively. Preclinical studies have reported that quercetin improves behavioral recovery by ameliorating in ammatory response after stroke (24,44). It has been demonstrated that MSCs improve neurological outcomes and modulate the immune cells, including microglia, and neutrophils, to ameliorate in ammatory responses in rats after ICH (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HE and Nissl staining also indicated the neuroprotection of IronQ-labeled MSCs is superior to MSCs and quercetin treatment, respectively. Preclinical studies have reported that quercetin improves behavioral recovery by ameliorating in ammatory response after stroke (24,44). It has been demonstrated that MSCs improve neurological outcomes and modulate the immune cells, including microglia, and neutrophils, to ameliorate in ammatory responses in rats after ICH (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 pathway dysfunctions increase the brain infarct area and neuronal damage after ischemic stroke [ 36 ]. Furthermore, Nrf2 is a vital molecular target for the neuroprotective effects of numerous natural products by suppressing oxidative stress [ 37 ]. We provided evidence that Nrf2 protein expression was decreased after cerebral ischemia/reperfusion; however, TPE and TPB considerably increased Nrf2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cornin, an iridoid glycoside derived from the fruits can increase proliferation, invasion, and lumen formation in vitro, resulting in angiogenesis. Cornin increased the proliferation of rat arterial smooth muscle cells (RASMC) and the expression of tissue homeostasis regulators like Wnt5a, Ī²-catenin, cyclin D1 and angiopoietin-1, confirming that it can reduce BBB leakage, promote angiogenesis and functional recovery after stroke (50).…”
Section: Protective Role Against Focal Cerebral Ischemia In Ratsmentioning
confidence: 93%